Clinical heterogeneity in a family with DKC1 mutation, dyskeratosis congenita and Hoyeraal-Hreidarsson syndrome in first cousins - Cristina Olivieri; Anna Mondino; Matteo Chinello; Alessandra Risso; Enrico Finale; Marina Lanciotti; Andrea Guala (MDPI AG, 2017)
Dyskeratosis congenita (DC) is an inherited bone marrow failure disorder characterized by mucocutaneous features (skin pigmentation, nail dystrophy and oral leukoplakia), pulmonary fibrosis, hematologic and solid malignancies. Its severe form, recognized as Hoyeraal-Hreidarsson syndrome (HHS), also includes cerebellar hypoplasia, microcephaly, developmental delay and prenatal growth retardation. In literature phenotypic variability among DC patients sharing the same mutation is wellknown. To our knowledge this report describes for the first time a family of DC patients, characterized by a member with features of classic DC and another one with some features of HHS, both with the same mutation in DKC1. Our family confirms again that one mutation can be associated with different phenotypes and different hematological manifestations. It's possible to speculate that there are likely to be patients who do not clinically fit neatly into either classical DC or HHS, but whose clinical features are due to mutations in DKC1 or in genes responsible for autosomal DC/HHS.